Isaiah fifty-three a devotional and expositional study - Young, Edward Joseph, 1907-68 (Grand Rapids, MI Eerdmans, 1952)
Includes bibliographical references.
Donated by Miss E. Cox, student, 1960.
Keywords: Bible. O.T. Isaiah LIII -- commentaries